Assessing the evidence of mental health promotion criteria in a pre-registration mental health nursing programme. Issue 3 (2nd September 2014) - Odro, A.B.; Dadzie, L.K.; Ryan, P.; Collins, D.; Lodoiska, R.
Abstract : Purpose: – This paper is about a single case study of a three-year BSc Mental Health Nursing degree programme based at a London University. The purpose of the paper is to evaluate the extent to which the programme sufficiently addresses the ten quality criteria developed by the "PROMISE" (2009) Mental Health Promotion Project. PROMISE (2009) is a European public health project funded by the European Commission and was conducted from 2009 to 2012. Its aim was the European-wide development of criteria and training guidelines in mental health promotion and recommended these should be integrated into the professional training curricula of nurses, psychiatrists, psychologists and social workers. Design/methodology/approach: – A content analysis method (Bryman, 2012) was used for this case study. This method allowed for a line-by-line scrutiny of the contents of the curriculum for evidence of the ten PROMISE quality criteria for mental health promotion (PROMISE project;http://promise-mental-health.com/training-guidelines.html ). Findings: – The findings revealed that the PROMISE (2009) project was not one of the four key documents stated as forming the basis for the design of the curriculum content. However, the study found evidence of the curriculum addressing the first PROMISE criterion of embracing the principles of mental health promotion in seven of the 14 modules (50 per cent) in the programme. In the first year of the programme five of the ten PROMISE quality criteria were embedded in two of the four modules. In year 2, quality criteria 1, 4 and 7 were addressed in the course content of four of the five modules (see Table I). In the final year of the programme PROMISE quality criteria 1, 2, 4 and 8 were embedded in the syllabus and assessment strategy in two out of the five final year modules. It was also found that quality criteria 2 and 9 were not included in any of the modules in the programme. Research limitations/implications: – This is a case study based on the content analysis of a single curriculum document in a London University. It is therefore not possible to make wide generalisation of its findings across the countries involved in the EU Promise project. However, it could be argued that it is possible to find a number of the key findings present in other UK University programmes that may be similar in structure to that selected for this study. The other limitation to this content analysis is that the evaluation process did not include accounts of the students' experience on the programme. This could have contributed significantly to the outcome of the evaluation exercise. Although the methodology used is simple, practical and relatively sound, it is not necessarily rigorous in terms of quantitative research methodology but arguably an acceptable contribution to the spectrum within qualitative research paradigm. Practical implications: – The emergence of the "PROMISE" criteria especially on a European-wide basis puts emphasis on the importance of mental health promotion in the training of health care professionals. This is expected to be achieved by the training institutions in the European Union. In the UK, this notion is well embraced in various health policy documents (e.g. "No Health Without Mental Health" DH 2011). In the case of the programme examined at one London University, work is required to ensure that a pervasive incorporation of mental health promotion strategies in the curriculum in order to help the students to become better equipped to understand and effectively apply the mental health promotion criteria in their work upon qualification. Originality/value: – This is one of the first papers to address the "PROMISE" project and the issue of incorporating mental health promotion criteria in a pre-registration mental health pathway training programme in a university in the UK.